Penjadwalan Ekonomis Pada Pembangkit Termal Dengan Menggunakan Particle Swarm Optimization - Muhammad Sidiq Dwi Putra; Sukma Abadi (Politeknik Negeri Ujung Pandang, 2023)
In this paper proposed optimal solution for Economic Dispatch (ED), problem has been suggested by Particle Swarm Optimization (PSO). PSO could schedule operating generator with to consider fuel cost, satisfying load demand and operational constraints so that optimal optimization results are obtained. In this article, the ED problem is formulated as a single objective problem by considering the fuel cost of generating units. Test cases, having no valve point effect without transmission loss has been operated by PSO. In order to view the effectiveness of the suggested algorithm, , it has been compared with other algorithms in the literature. Results show that the PSO is more powerful than other algorithms.